OC19: Visual evoked potentials monitoring during neurosurgical operations: optimizing the protocol. (March 2022) - Levin, E.; Vasyatkina, A.; Semin, P.; Kiselev, R.
Abstract : Visual evoked potentials (VEPs) are used for intraoperative neurophysiological monitoring (IONM) during surgeries involving visual system. But unlike other IONM modalities, no standards have been yet developed for the intreoperative VEPs monitoring. Here we consider VEPs registration parameters contributing to their successful and useful monitoring. Methods. 144 consecutive surgeries (288 eyes) performed using VEPs monitoring were analyzed retrospectively. Stimulation: flash intensity 25000 lx, duration 10 ms, frequency ∼1 Hz, 20–100 responses averaged. 7 electrodes placed, three pairs chosen. Bandpass filtering: [10-20] – [200-400] Hz (chosen individually). Alarm: standard 10–50% criteria. Anesthesia: propofol – 110 surgeries, sevoflurane – 14, combined – 20. In 27 surgeries, propofol-to-sevoflurane transition performed after dura closure. Results. Chosen electrode pairs: Oz-A1&Oz-A2 in 45% of surgeries, O1/O2/Oz-CPz in 25%, O1/O2/Oz-Fz in 24%. Chosen frequency filters: 100–400 Hz (200 Hz in 67%) low-pass, 5–20 Hz (10 Hz in 59%) high-pass. Anesthesia effects: 5, 9% unresponsive non-blind eyes for propofol and 18, 5% for sevoflurane anesthesia. After propofol-to-sevoflurane transition VEPs disappeared in 22% of cases. Alarm criteria had been reached for 73 eyes. Full recovery observed later in 62%, partial in 23%, no recovery in 15% of cases. Postoperative visual impairments among eyes with: successful VEPs monitoring without alarms – 3%, full recovery after alarms – 7%, incomplete or no recovery – 23%, unobtainable VEPs – 14%. Conclusions. Optimal parameters of VEPs recording for IONM should be selected individually and differs from the standards for clinical diagnostics. VEPs recording under (low-to-moderate-dose) sevoflurane is often possible, but the propofol anesthesia is preferable.